Architecture for Virtualization and Collaboration in Edge Computing: an implementation based on FIWARE building blocks - Alves, Marcelo Pitanga; Delicato, Flávia Coimbra; dos Santos, Igor Leão; Pires, Paulo F. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2020: Anais do XXXVIII Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc.2020.12318, 2020)
Edge Computing is a novel paradigm that allows moving the computation closer to the end-users and/or data sources. In this paper, we present a three-tier architecture for virtualization and collaboration of Virtual Nodes that leverages the Edge tier to meet those emerging IoT applications that demand requirements such as low latency, geo-localization, and energy efficiency. Besides the Edge tier, our implementation is based on the mix of lightweight virtualization and microservices using the building blocks from the FIWARE platform to interact with the physical environment. Furthermore, we presented two experiments to assess our architecture under severe and realistic conditions, regarding the network latency and fault-tolerance.